Coordination models and languages 13th International Conference, COORDINATION 2011, Reykjavik, Iceland, June 6-9, 2011. Proceedings - Meuter, Wolfgang De; Roman, Gruia-Catalin (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Coordination Models and Languages, COORDINATION 2011, held in Reykjavik, Iceland, in June 2011, as one of the  DisCoTec 2011 events. The 14 revised full papers presented were carefully reviewed and selected from 35 submissions. The conference focuses on the design and implementation of models that allow compositional construction of large-scale concurrent and distributed systems, including both practical and foundational models, run-time systems, and related verication and analysis techniques.